Mindfulness based interventions for depression and anxiety in Asian Population: A systematic review - Thapaliya, S.; Upadhyaya, K.D.; Borschmann, R.; Kuppili, P.P. (Journal of Psychiatrists' Association of Nepal, 2018)
Introduction: Mindfulness based interventions (MBIs) have emerged as effective interventions for various psychiatric conditions including depression and anxiety. Asia being home to Buddhist tradition, it will be interesting to explore the trend and efficacy of MBIs in Asian population in Asian settings. The aim of this study is to perform a systematic review of mindfulness based interventions (MBIs) for management of depression and anxiety (disorders or symptoms) in Asian population.Material And Method: Two researchers independently searched for literature published between January 2007 to December 2018 in Medline, Google Scholar, PsychInfo and Cochrane library using the search terms - ‘Mindfulness/Vipassana’ combined with ‘meditation’, ‘intervention’ ‘therapy’, ‘depression', ‘anxiety’ ‘Asia’ etc. Further, publications were also identified from the references recited in the retrieved articles. After screening 185 articles and applying the eligibility criteria, 40 articles were finally selected for the systematic review.Results: Out of 40 selected articles, 33 articles were controlled trials and 7 had a pre-post test design without any control group. Most of the published studies have evaluated MBCT and MBSR for depressive and anxiety symptoms in different settings. Some of the studies have tested traditional Buddhist meditation and modified models. Overall, MBCT and MBSR seem to be efficacious over ‘routine treatment’ or ‘no treatment’ control for reducing depressive and anxiety symptoms at the end of the treatment. Studies which have modified MBIs based on MBCT/MBSR models have also demonstrated their feasibility and short term efficacy in specific populations like medical professionals with evidence for short term efficacy.Conclusion: Overall, there is emerging evidence of MBIs for depression and anxiety across diverse settings in Asia. Future research should address methodological limitations of current research to strengthen the evidence.